2022
DOI: 10.1007/s40744-022-00454-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Belimumab in Systemic Lupus Erythematosus: A Systematic Literature Review

Abstract: Introduction Belimumab is a recombinant human monoclonal antibody that binds to soluble B-lymphocyte stimulator and inhibits its biological activity. Since receiving approvals for the treatment of systemic lupus erythematosus (SLE), several observational studies have investigated the effectiveness of belimumab in the real-world setting. This study reports a systematic review and meta-analysis of the literature to evaluate the real-world effectiveness of belimumab for the treatment of SLE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In an earlier practice-based study, we demonstrated good tolerability and a significant decline in disease activity in SLE patients under belimumab treatment, irrespective of the baseline serological status ( 12 ). Likewise, a number of other cohorts from different settings and regions of the world have evaluated the use of belimumab in adult SLE patients ( 7 , 13 ), focusing primarily on the frequency and predictors of treatment response including disease duration, baseline disease activity, type of manifestations and pre-existing organ damage ( 14 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier practice-based study, we demonstrated good tolerability and a significant decline in disease activity in SLE patients under belimumab treatment, irrespective of the baseline serological status ( 12 ). Likewise, a number of other cohorts from different settings and regions of the world have evaluated the use of belimumab in adult SLE patients ( 7 , 13 ), focusing primarily on the frequency and predictors of treatment response including disease duration, baseline disease activity, type of manifestations and pre-existing organ damage ( 14 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the phase Ia, first-in-human, SAD study (NCT02618967), healthy subjects (N = 65; age 18-65 years) were randomized at a 3:1 ratio to receive a single subcutaneous (s.c.) dose of rozibafusp alfa (7,21,70,140,210,420, or 700 mg) or placebo, with a 15-week follow-up period.…”
Section: Clinical Study Designs and Participantsmentioning
confidence: 99%
“…3 Biologic treatment for SLE by single target inhibition of the BAFF pathway (belimumab) was approved in 2011 and has demonstrated efficacy in clinical trials and in real world settings. [4][5][6][7] More recently, inhibition of interactions between ICOS and ICOSL, as shown in early clinical trials with the anti-ICOSL antibody AMG 557, have demonstrated potential efficacy for the treatment of SLE. 8,9 There are no approved therapies that target BAFF and ICOSL simultaneously.…”
mentioning
confidence: 99%
“…15 In their systematic review and meta-analysis, Huang et al demonstrated the overall effectiveness of belimumab in SLE in the real-world context, including a reduction of corticosteroid dose. 16 While previous research has evaluated data from randomised trials, retrospective claims and prospective chart reviews, the present study is unique in that it brings the perspective of community rheumatologists by leveraging real-world data from a large US rheumatology network. It seeks to evaluate patterns of OCS use before and during treatment with belimumab.…”
Section: Lupus Science and Medicinementioning
confidence: 99%